Partial incorporation of black jelly mushroom (Auricularia polytricha) as a plant-based ingredient in the production of hybrid patties using meat from different species - Abdul Wahab, Nurdamia Qaisara; Pangestika, Leonie Margaretha Widya; Ismail-Fitry, Mohammad Rashedi (Oxford University Press, 2024)
The impact of meat replacement with black jelly mushrooms as a means to produce hybrid patties using meat from different species (chicken-MCP, beef-MBP, mutton-MMP and buffalo-MBOP) was investigated. For this purpose, 50% of the meat was replaced with black jelly mushrooms. A patty with 100% mushroom (CMP) was observed as a control. Proximate composition, water holding capacity (WHC), cooking yield, shrinkage, pH, gel strength, colour, texture, microstructure and sensory acceptance of the patties were analysed. MBP had the highest WHC (88.51%) and gel strength (24.89 N) compared to other patties (P < 0.05). MBP exhibited a less compact and dense structure compared to other patties. Simultaneously, it is characterised as the least in hardness but the highest in chewiness and cohesiveness. The sensory evaluation highlights MBP as the most preferred, particularly for texture. In conclusion, black jelly mushrooms are suitable to be mixed with beef to produce alternative patties.